EMOTIONAL INTELLIGENCE AND LEARNING BEHAVIOR ON UNDERSTANDING OF PUBLIC ACCOUNTING SECTOR ACCOUNTING STUDENTS - Tituk Diah Widajantie; Marseto Marseto; Sofie Yunida Putri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research was conducted to examine whether there is an influence between emotional intelligence and learning behavior on public sector accounting understanding. The population used was public sector concentration accounting students in Universitas Pembangunan Nasional “Veteran” Jawa Timur. The data collection technique used was primary data by distributing questionnaires to respondents. This study’s data processing method used the Partial Least Square. In this case, the result was that Emotional Intelligence and Learning Behaviour significantly influence Public Sector Accounting Understanding. Emotional intelligence, measured by self-knowledge, self-control, motivation, empathy, and social skills, significantly affects understanding public sector accounting. Learning behavior, as measured by the habit of attending lessons, the habit of reading books, visits the library, and the habit of taking exams, has a significant effect on the understanding of public sector accounting.